PERFECTIVAS EN EL CONTROL BIOLÓGICO DE NEMATUS OLIGOSPILUS FOERSTER (= N. DESANTISISMITH) (HYMENOPTERA: TENTHREDINIDAE), PLAGA DE SAUCES EN LA ARGENTINA Y CHILE - Alderete, Mariela del Carmen; Fidalgo, Patricio; Ovruski, Sergio (Acta Entomológica Chilena, 2022)
Nematus oligospilus Foerster (cited from Argentina and Chile as N. desantisi Smith) is a species native to the Holartic Región, where it occurs widely throughout Eurasia and North America affecting Salix spp. It was accidentally introduced in Argentina and Chile in the 80’ s, in South Africa in 1993 and more recently in New Zeland in 1997. A review of taxonomic structure of parasitoids known to attack Nematus and the related Pristiphora species in the Holarctic región shows that Campopleginae (Olesicampe spp.) and Ctenopelmatinae (,Mesoleius spp.) as well as other monophagous and oligophagous ichneumonids (specially Thryphoninae) along with some oligophagous and poliphagous tachinids (Goniinae and Dexiinae) are the most important components of the complex of natural enemies associated with these Nematine sawflies. From our study of the parasitoid guilds associated with Nematus and Pristiphora in their home range we recommended that some these natural enemies are introduced into Argentina and Chile as part of a long